Antibacterial Properties and Mechanism of Lysozyme-Modified ZnO Nanoparticles - Yuan, Kangrui; Liu, Xiaoliu; Shi, Jianxin; Liu, Wei; Liu, Kun; Lu, Hongmei; Wu, Dudu; Chen, Zhi; Lu, Chengyu (Frontiers in Chemistry, 2021)
The lysozyme-modified nanoparticles (LY@ZnO NPs) were synthesized by the reduction–oxidation method, and the morphology and structure of LY@ZnO were analyzed by Fourier transform infrared (FTIR) spectroscopy, powder X-ray diffraction (XRD), scanning electron microsclope (SEM), and particle size analysis. The antibacterial effects of LY@ZnO against Escherichia coli (E. coli, Gram-negative bacteria) and Staphylococcus aureus (S. aureus, Gram-positive bacteria) were discussed by measuring the zone of inhibition (ZOI) and growth inhibition. The antimicrobial experiments showed that the LY@ZnO NPs possessed better antibacterial activity than ZnO. Besides, the antibacterial mechanism of LY@ZnO was also investigated, which was attributed to the generation of reactive oxygen species (ROS). Furthermore, the toxicities of LY@ZnO in vivo and in vitro were discussed by the cell counting kit-8 method and animal experiments, showing that LY@ZnO possessed excellent biocompatibility. Finally, the therapeutic effect of LY@ZnO on a rat skin infection model caused by methicillin-resistant Staphylococcus aureus (MRSA) was also studied, which exhibited good anti-infective activity. Our findings showed that LY@ZnO possessed remarkable antibacterial ability due to its excellent membrane permeability and small particle size. Besides, LY@ZnO also exhibited certain stability and great safety, which showed tremendous prospects for microbial infection in patients. It would also be helpful for a better understanding of the enzyme-modified nanomaterials against bacteria.